Tinjauan Hukum Ekonomi Islam Tentang Jual Beli Pasir Dari Hasil Penambangan - Gaussian, Gini; Maulid, Ecep Imam (STAI Al Musaddadiyah Garut, 2025)
This study aims to analyze the practice of buying and selling sand from mining activities in the perspective of Islamic Economic Law. In this context, sand is a commodity widely used in various development sectors but requires legal attention, particularly in relation to sharia principles. The research problems are formulated as follows: (1) how the sand mining practices are carried out in Ciojar River, Banyuresmi District, and (2) how Islamic Economic Law views the sand mining business practices in Ciojar River, Banyuresmi District. The objectives of this study are: (1) to examine the practices of sand mining in Ciojar River, Banyuresmi District, and (2) to analyze the perspective of Islamic Economic Law on sand mining practices in Ciojar River, Banyuresmi District. This study employs a qualitative approach with a descriptive-analytical method, examining various practices of sand trading from the perspective of Islamic Economic Law and its impacts on miners, society, and the environment. The findings reveal that although sand trading transactions are generally permissible, several elements need improvement to better comply with Islamic sharia principles and local government regulations, especially concerning licensing, management rights in mining sustainability, and fair profit distribution. This study recommends that sand mining and trading practices be more properly regulated in accordance with Islamic legal principles to achieve social justice and environmental sustainability. Keywords: Islamic Economic Law, Sand Trade, Mining, Sharia Principles.